Analysis of Problem-Solving Skills and Sustainable Consumption Understanding Among Upper Elementary Students in Primary School - Wulan Rahmafinia; Ari Widodo; Sardin Sardin (Journal of Innovation and Research in Primary Education, 2026)
This study investigates upper elementary students' sustainable consumption understanding and problem-solving skills concerning single-use plastic food packaging waste. Employing a quantitative survey design, the research involved 53 fifth- and sixth-grade students from public and private primary schools in Sumedang, Indonesia. Data were collected through a 34-item Likert-scale questionnaire assessing sustainable consumption across knowledge, behavioral, and socio-emotional indicators, and 10 contextual open-ended items evaluating problem-solving abilities using the IDEAL framework. Descriptive and inferential statistics, including Pearson correlations, independent t-tests, and one-way ANOVA, were employed for analysis. Results reveal robust sustainable consumption understanding in knowledge (78%) and socio-emotional domains (80%), yet behavioral indicators trail at 70%, evidencing a pronounced attitude-behavior gap. Female students, sixth graders, and private school attendees consistently outperformed their counterparts across all indicators. Conversely, problem-solving proficiency remains critically deficient, with 60.37% of students categorized as weak (mean scores 1.90–2.02 on a 4-point scale), particularly in problem identification and solution planning stages. These findings demonstrate that while students possess adequate environmental awareness, they lack the analytical competencies necessary to translate knowledge into sustainable practices. The study underscores the imperative for experiential, project-based pedagogies integrating problem-solving skill development to bridge knowledge-behavior gaps and cultivate responsible consumption behaviors aligned with Sustainable Development Goal 12.